Acute haemodynamic effects of oral prenalterol in severe heart failure. Issue 1 (July 1984) - Petch, M C; Wisbey, C; Ormerod, O; Scott, C; Goodfellow, R M
Abstract : The acute haemodynamic effects of oral prenalterol were studied in 14 patients with severe heart failure (NYHA class III) due to ischaemic heart disease. All had received treatment with digoxin, diuretics, and in most cases vasodilators. Prenalterol was administered at two hourly intervals to give cumulative doses of 20, 50, and 100 mg and mean plasma concentrations of 53, 97, and 175 nmol/l. Haemodynamic measurements were made two hours after each dose with Swan-Ganz catheterisation; cardiac output was measured by thermodilution. There were no significant changes in heart rate, mean arterial pressure, or pulmonary artery diastolic pressure after the drug. Cardiac index rose significantly after 50 mg and 100 mg prenalterol. Oral prenalterol has a beneficial short term haemodynamic effect in patients with severe heart failure. If this effect is sustained prenalterol may be of value in the long term management of patients with this disabling condition.